Kurds in the Middle East in the context of plurality of identities - Al-Absi, Marwan; Al-Absiová, Eva (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper analyzes the ethnic, linguistic and religious aspects of the Kurdish region. It explains the issue of the tribal identity of Kurdish communities in the Middle East and points to the phenomenon of tribalism as a key factor affecting the degree of ethnic and political consistency of Kurdistan.
Keywords: Kurds; Kurdish; Iraqi Kurdistan; Kurdish identity; tribalism